1996
DOI: 10.1038/382541a0
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of apoptosis by the leukaemia-associated E2A–HLF chimaeric transcription factor

Abstract: The E2A-HLF (for hepatic leukaemia factor) fusion gene, formed by action of the t(17;19) (q22;p13) chromosomal translocation, drives the leukaemic transformation of early B-cell precursors, but the mechanism of this activity remains unknown. Here we report that human leukaemia cells carrying the translocation t(17;19) rapidly died by apoptosis when programmed to express a dominant-negative suppressor of the fusion protein E2A-HLF, indicating that the chimaeric oncoprotein probably affects cell survival rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 26 publications
5
110
1
1
Order By: Relevance
“…As a consequence, E2a-Hlf binds and activates transcription through DNA sites di erent from those recognized by E2a-Pbx1 or wild type E2a proteins (Hunger et al, 1994;Inaba et al, 1994). Recent studies have shown that forced expression of E2a-Hlf prevents precursor B cells of the BaF3 cell line from undergoing apoptosis in response to IL3 withdrawal (Inaba et al, 1996). These ®ndings raise the possibility that Hlf targets may equate with survival whereas Pbx targets may equate with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, E2a-Hlf binds and activates transcription through DNA sites di erent from those recognized by E2a-Pbx1 or wild type E2a proteins (Hunger et al, 1994;Inaba et al, 1994). Recent studies have shown that forced expression of E2a-Hlf prevents precursor B cells of the BaF3 cell line from undergoing apoptosis in response to IL3 withdrawal (Inaba et al, 1996). These ®ndings raise the possibility that Hlf targets may equate with survival whereas Pbx targets may equate with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the expression of E2A-HLF in NIH 3T3 cells induced anchorage-independent cell growth in soft agar and rendered these cells tumorigenic in nude mice (Yoshihara et al, 1995;Inukai et al, 1997). In addition, using a zinc-inducible system, we showed that E2A-HLF expression protects interleukin 3-dependent hematopoietic cells from interleukin 3 deprivation-induced apoptosis (Inaba et al, 1996). Moreover, by a representational difference analysis, several downstream candidate genes of E2A-HLF were cloned, such as annexin II (Matsunaga et al, 2003), annexin VIII and sushi-repeat protein upregulated in leukemia (SRPUL; Kurosawa et al, 1999), two Groucho-related genes, Grg2 and Grg6 (Dang et al, 2001), and a gene encoding a zinc-finger transcription factor, Slug .…”
Section: Introductionmentioning
confidence: 89%
“…For instance, an aberrant expression of Bcl-2 protein is known to protect cells from death rather than stimulating cell cycle transition (Korsmeyer, 1992). E2A-HLF fusion protein created by the t(17;19)(q22;p13) translocation prevents hematopoietic cells from apoptosis (Inaba et al, 1996). A loss of function mutation of NF1, a stimulator of RasGTPase, is associated with JCML (juvenile chronic myelogenous leukemia) (Bollag et al, 1996;Largaespada et al, 1996), possibly by enhancing the basal activity of the Ras pathway (Largaespada et al, 1996).…”
Section: Introductionmentioning
confidence: 99%